Perceived effect of training and development programmes on employee performance in Mamelodi Clinics, Gauteng Province - Legong, Mabina Madimetsa (My University, 2022)
The purpose of this study was to investigate the effects of training and development on employee performance at Mamelodi Clinics, Gauteng Province. This study was guided by the following objectives. To determine the perceived effect of training and development courses on skills development of professional nurses in the Mamelodi clinics, Gauteng Province. To explore the perceived effect of training and development courses on the performance of professional nurses in the Mamelodi clinics, Gauteng Province. To examine which of the attended short courses are more effective in improving the skills of professional nurses. To find out which short courses, according to the professional nurses in the study, were found to be ineffective and unnecessary. The study was of importance to future researchers and academicians as it added new insight into the existing information with regards to employee training and development. It also provided the department of health, both nationally and provincially with an understanding of successes and challenges inherent to training and development and their corresponding effect on employee performance. As a result, this had a contribution towards how training and development are carried out within the organisation. A qualitative research design was deployed in this study to allow investigation of the possible relationship between training and development as well as to establish a comparison between the two. The study population was 45 staff of Mamelodi Clinics which were approved for this study. The data was collected through a questionnaire. Percentages, means, cross-tabulation were used as means of data analysis. The findings were presented using tables and figures. In terms of training and development, the study was able to show that all Mamelodi Clinics under department of health Gauteng Province, has a range of training programmes for different staff of their clinics, and are of high quality standard and very effective. As a result, employee skills, overall performance of staff, and general competence of the employee has sharply increased due to training and development v methods and strategies put in place by department of health, both provincially and nationally. The study showed that in terms of employee performance and motivation, training and development programmes help in increasing employee motivation and thus performance. Employees are thus able to successfully be aligned with the goals, aims and missions of the clinics and the department of health, as well as the Batho Pele principles. The study concludes that training and development have positive effects on employees. The study was able to find that within the clinics, employees are given adequate chance to engage in training and development courses. The study concludes further that more training and development programmes should be undertaken. The study recommends that there should be regularly assessments on employees and their subsequent need for further training and development courses in order to increase employee satisfaction and performance.
Thesis (MBA.) -- University of Limpopo, 2022
Keywords: Employee performance; Training; Development; Skills development; Employees -- Rating of; Performance -- Evaluation; Employees -- Training of; Goal setting in personnel management